Academic motivation and emotions are experienced in learning situations, so let's study them. Introduction to the special issue. (October 2022) - Dietrich, Julia; Schmiedek, Florian; Moeller, Julia
Abstract: The learning process is affected by manifold individual and contextual influences, among them motivation and emotion. Rather than being stable over time and the same under all circumstances, academic motivation and emotions vary and change in complex and dynamic ways. Understanding such processes requires research approaches that capture students' inthe-moment experiences with situation-specific assessments. This endeavor is at the core of the present Special Issue. Based on intensive longitudinal data, the articles aim to shed light on the situational impact on students' motivational and emotional experiences and behavior. This introduction summarizes reasons why situational assessments and situation-aware analyses are needed and points out the challenges accompanying such situation-focused methods. As an avenue for future method and theory development, we then propose integrating some dynamic systems ideas when studying the short-term dynamics of emotions and motivation in learning situations.